P56 Use of the Tuberculin Skin Test and Tspot For Screening Prior to TNF Antagonist Therapy Identifies Additional Patients Eligible For Chemoprophylaxis Compared to Use of Risk Assessment Strategies Alone. (19th November 2012) - Manalan, K; Singanayagam, A; Molyneaux, PL; George, PM; Connell, DW; Lalvani, A; Wickremasinghe, M; Kon, OM
Abstract : Patients: with rheumatological disease who are treated with TNF antagonist therapy are at increased risk of reactivating latent tuberculosis infection (LTBI). It is believed that immunosuppressant therapy in this group may reduce the reliability of the tuberculin skin test (TST) due to a high incidence of anergy. The value of interferon gamma release assays in this setting is also unclear. The aim of this study was to assess the value of a combination of the TST and Tspot for screening in patients on immunosuppressants and compare to the BTS-recommended approach, which advocates treatment decisions based on risk stratification. Methods: Adult patients referred for TB screening to a tertiary centre prior to commencement of Anti-TNF therapy were included in the study. All patients received a uniform screening protocol of clinical history, chest radiograph, stratification of TB risk (by ethnicity and age according to BTS guideline risk-tables), TST and Tspot . Results: There were 137 patients included with 116 (84.7%) taking immunosuppressant medication at the time of screening. Of the sub-group on immunosuppressants, 17 patients (14.7%) had positive TST results (5 patients with result >15mm in presence of BCG, 12 patients with result >5mm in absence of previous BCG). Of this sub-group with positive TST results, 12 patients (70.6%) would not have been treated according to risk-stratification tables. Of the sub-group on immunosuppressants, 25 patients (21.6%) had positive Tspot results and 1 patient had an indeterminate result. Of this subgroup with positive Tspot results, 17 patients (68%) would not have been treated according to risk-stratification tables. When comparing strategies, use of risk-stratification tables alone would lead to 26 patients being treated with chemoprophylaxis. Addition of either positive TST and/or positive Tspot in patients not identified by risk stratification method led to an additional 22 patients eligible for treatment (9 patients Tspot positive alone; 7 patients TST positive alone; 6 patients double positive). Conclusion: Performing both a TST and Tspot in patients on immunosuppressants prior to commencement of Anti-TNF screening gives an additional yield of potential LTBI when risk assessment strategies alone would not have identified these.